Ex-vivo biomechanics of repaired rat intervertebral discs using genipin crosslinked fibrin adhesive hydrogel. (2nd December 2020) - Fujii, Kengo; Lai, Alon; Korda, Nimrod; Hom, Warren W.; Evashwick-Rogler, Thomas W.; Nasser, Philip; Hecht, Andrew C.; Iatridis, James C.
Abstract: Microdiscectomy is the current standard surgical treatment for intervertebral disc (IVD) herniation, however annulus fibrosus (AF) defects remain unrepaired which can alter IVD biomechanical properties and lead to reherniation, IVD degeneration and recurrent back pain. Genipin-crosslinked fibrin (FibGen) hydrogel is an injectable AF sealant previously shown to partially restore IVD motion segment biomechanical properties. A small animal model of herniation and repair is needed to evaluate repair potential for early-stage screening of IVD repair strategies prior to more costly large animal and eventual human studies. This study developed an ex-vivo rat caudal IVD herniation model and characterized torsional, axial tension–compression and stress relaxation biomechanical properties before and after herniation injury with or without repair using FibGen. Injury group involved an annular defect followed by removal of nucleus pulposus tissue to simulate a severe herniation while Repaired group involved FibGen injection. Injury significantly altered axial range of motion, neutral zone, torsional stiffness, torque range and stress-relaxation biomechanical parameters compared to Intact. FibGen repair restored the stress-relaxation parameters including effective hydraulic permeability indicating it effectively sealed the IVD defect, and there was a trend for improved tensile stiffness and axial neutral zone length. This study demonstrated a model for studying IVD herniation injury and repair strategies using rat caudal IVDs ex-vivo and demonstrated FibGen sealed IVDs to restore water retention and IVD pressurization. This ex-vivo small animal model may be modified for future in-vivo studies to screen IVD repair strategies using FibGen and other IVD repair biomaterials as an augment to additional large animal and human IVD testing.